Access to the judiciary. Backward selection - Andrés Ibáñez, Perfecto (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
In Spain, the system of competitive examinations for the selection and training of judges, which was introduced in the early 1860s, is still in force. It involves a programmed of several hundred topics covering fundamental legal subjects, reflecting a way of understanding the law that is alien to the current legal system of a constitutional state. Preparation for the admission tests consists of memorizing the syllabus, which is essentially made up of notions of positive law, from which the epistemology of factual judgement is completely absent. The exam consists of the mechanical recitation of certain topics. Those who are selected take a course at the "Judicial School", but this is based on the idea that the training should be practical, because the theory has already been acquired. The result is a clear legal and cultural deficit that can only be overcome by voluntary personal study efforts to compensate for it.